2010
DOI: 10.1109/jstqe.2010.2040464
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Solar Cells: Recent Developments and Outlook

Abstract: Abstract-Solution processed photovoltaic devices are an attractive alternative to costly inorganic semiconductor based conventional photovoltaics. Solution processable organic photovoltaic systems are affected by low carrier mobility, lifetime issues under ambient conditions and limited optical absorption due to the high bandgaps of organic materials. Nanostructured inorganic materials promise to alleviate some of these drawbacks, by enabling the hybrid systems to perform better in a commercial perspective. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 108 publications
(106 reference statements)
0
36
0
Order By: Relevance
“…OPVs incorporating these rr-P3HT/s-SWNT networks as the HTL demonstrate the best large area (70 mm 2 ) carbon nanotube incorporated organic solar cell to date with a power conversion efficiency (PCE) of 7.6%. This signifies the strong capability of nanohybrids as an efficient hole extraction layer and we believe that dense nanohybrid networks have the potential to replace expensive and material scarce inorganic transparent electrodes in large area electronics towards the realization of low-cost flexible electronics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OPVs incorporating these rr-P3HT/s-SWNT networks as the HTL demonstrate the best large area (70 mm 2 ) carbon nanotube incorporated organic solar cell to date with a power conversion efficiency (PCE) of 7.6%. This signifies the strong capability of nanohybrids as an efficient hole extraction layer and we believe that dense nanohybrid networks have the potential to replace expensive and material scarce inorganic transparent electrodes in large area electronics towards the realization of low-cost flexible electronics.…”
mentioning
confidence: 99%
“…Single walled carbon nanotubes (SWNT) with its unique electronic transport properties, continues to contribute to rapid advances in the fields of flexible electronics 1 , photovoltaics 2 , thin film transistors (TFT) 3 and biosensors. 4 Traditionally, as produced carbon nanotubes are known to form bundles which prevents the unique properties of individual carbon nanotubes being realized.…”
mentioning
confidence: 99%
“…Of the many types of solar-energy converting systems, organic photovoltaics have attracted significant interest due to their low cost, light weight and the printable nature on flexible substrates. [1][2] Bulk heterojunction (BHJ) organic solar cells are one of the material systems extensively investigated for this purpose, where an electron donating conjugated polymer and an electron accepting small molecule fullerene are been blended to form the active material. 1,3 Recent breakthroughs in the development of low bandgap polymers for harvesting of photons from the red 4 to the near infrared 5 .…”
Section: Bodymentioning
confidence: 99%
“…The performance of BHJ organic solar cells is driven by the following key processes: (1) absorption of a significant fraction of photons from the solar spectrum, (2) generation of excitons and their dissociation at the donor (D) -acceptor (A) interface (giving rise to the internal quantum efficiency), (3) transport of the free charges towards contacts, and, (4) extraction of these charges at the contacts to generate useful power (the external quantum efficiency or IPCE). Processes (1)-(3) have been extensively investigated, with engineering of the interfacial charge transport layers receiving attention due to its importance in the light coupling 6 and charge extraction in these devices 7 .…”
Section: Bodymentioning
confidence: 99%
“…For improving the operational parameters of the organic matrix and to give unique properties to the final product, the organic-inorganic composite materials are formed [6][7][8][9]. The titanium-containing organic-inorganic materials are attracted much attention due to their potential use as membranes, photocatalysts, solar cells and elements for optical devices [10][11][12]. Also, the recent studies have demonstrated perspectives in using the titaniumcontaining hybrid materials in photonics, especially for the laser 3D microstructuring, and for optical data storage [13].…”
Section: Introductionmentioning
confidence: 99%